Komunitas Berbaju Hitam: Sejarah, Perempuan, dan Pendidikan dalam Masyarakat Adat Tana Towa Kajang, Sulawesi Selatan - Sarkawi B. Husain; Lina Puryanti; Adi Setijowati (Jurnal Sejarah Citra Lekha, 2021)
Studies on the Ammatowa indigenous people have been carried out by several researchers. Unfortunately, none of these studies have focused on the role and position of women in the Ammatowa people, both in their daily lives and in regard  to education. Therefore, this study fills that void. This study aims to identify the position and role of women in the life of the Ammatowa people; what specific roles are performed by women in customary areas; and how the traditions are still firmly held provide space for women to express themselves. As a study of a unique community, this study uses an ethnographic approach, by collecting, classifying, and analyzing the various positions of women in the Ammatowa Kajang community. In the traditional structure of Tana Towa, women have an important, strategic and respected position. In the structure of these customs, there is an important role played by a woman called Angrota who has the task and responsibility of preparing all the needs for traditional ceremonies, facilitating the selection of Ammatowa and inaugurating them. In the economic aspect, women have an important role in supporting the family’s financial, such as weaving, selling in the market, and farming. Meanwhile, education for Tana Towa women is still a major issue that needs serious attention. It is because the education world is related to issues of customs, and the family economy.